2023
DOI: 10.3847/2041-8213/acb261
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectropolarimetry of Binary Asteroid Didymos–Dimorphos before and after the DART Impact

Abstract: We have monitored the Didymos–Dimorphos binary asteroid in spectropolarimetric mode in the optical range before and after the DART impact. The ultimate goal was to obtain constraints on the characteristics of the ejected dust for modeling purposes. Before impact, Didymos exhibited a linear polarization rapidly increasing with phase angle, reaching a level of ∼5% in the blue and ∼4.5% in the red. The shape of the polarization spectrum was anticorrelated with that of its reflectance spectrum, which appeared typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…This study presents new ground-based telescopic data from September 26 through November 1. The data presented expand upon previously reported ejecta results (Bagnulo et al 2023;Graykowski et al 2023;Li et al 2023;Opitom et al 2023) which have shown the evolution of the ejecta to be a significantly more complex and long-lasting process than anticipated prior to impact. This work combines data from 12 Earth-based facilities that were collected with denser temporal sampling and with wider fields of view than the other published studies.…”
Section: Introductionsupporting
confidence: 85%
“…This study presents new ground-based telescopic data from September 26 through November 1. The data presented expand upon previously reported ejecta results (Bagnulo et al 2023;Graykowski et al 2023;Li et al 2023;Opitom et al 2023) which have shown the evolution of the ejecta to be a significantly more complex and long-lasting process than anticipated prior to impact. This work combines data from 12 Earth-based facilities that were collected with denser temporal sampling and with wider fields of view than the other published studies.…”
Section: Introductionsupporting
confidence: 85%
“…The DART spacecraft impacted Dimorphos at 23:14 UT on 2022 September 26. Our observations span a period from about 1 month before to almost 4 months after the impact, with a number of the VLT observations being made hand in hand with spectropolarimetric observations (Bagnulo et al 2023)-this has been indicated in the observing log. Considering the entire observing campaign, we have observed the asteroid system in three stages.…”
Section: Observationsmentioning
confidence: 92%
“…Therefore, we first converted our R-and B-band measurements to the V band before using the above expression to calculate the geometric albedo. According to the spectropolarimetric measurements of Bagnulo et al (2023), the ratio between measurements in the V and R bands are nearly constant with phase angle, i.e., (P Q (V ) − P Q (R))/P Q (R) ∼ 0.05, as well as between the V and B bands,…”
Section: Polarimetric Phase Curvementioning
confidence: 99%
“…Apart from the plume, a fraction of the ejected mass was emitted at significantly lower speeds, forming the ejecta pattern and tail that could be seen on the earliest images acquired from ground-based observatories (Bagnulo et al 2023;Opitom et al 2023) and the HST . Our purpose is to characterize the dust properties of this mostly slow-moving ejecta, the ejection velocities, the size distribution, and the ejected mass using Monte Carlo models to simulate the motion of the particles in the spatial region near the binary system.…”
Section: Introductionmentioning
confidence: 99%